EFFECT OF CUSTOMER RELATIONSHIP MANAGEMENT (CRM) PROGRAM ON CUSTOMER LOYALTY - Lutpiyani, Lutpiyani; Prahesti, Riska Tyas (Transpublika Publisher, 2025)
The existence of competition among companies today, which can no longer be avoided, has made Public Relations (PR) one of the vital components in the success of modern companies in this digital era. One of the main roles of PR is to implement Customer Relationship Management (CRM) and maintain and enhance consumer loyalty. A business needs to implement CRM to enhance the overall customer experience throughout the organization. This includes all interactions, whether in-person or online, and covers everything from pre-sales activities to the experience with products and services, as well as post-sales support. As such, existing customers will be able to influence other customers that the company's service is good. PT. Telkom Indonesia implements a CRM to better recognize and understand their customers so that the business can respond to customer needs quickly and accurately. PT. Telkom Indonesia provides a product called IndiHome and continues to innovate to meet the community's need for better internet services. This research aims to determine whether there is an influence of the Customer Relationship Management (CRM) Program on Customer Loyalty. This research uses a positivistic paradigm with a quantitative method, employing non-probability sampling techniques with specific criteria to determine the sample and distributing questionnaires through Google Forms, followed by data processing using SPSS. The sample in this study consisted of 100 respondents using the Taro Yamane formula. The results of this study prove that Customer Relationship Management (CRM) has a very strong influence on customer loyalty at PT. Telkom Indonesia.